PENGARUH LUAS LAHAN PERTANIAN DAN BIAYA PEMELIHARAAN TERHADAP PENDAPATAN PETANI (STUDI KASUS DESA KEPENUHAN RAYA) - Hamdi Sari Maryoni (Fakultas Ekonomi Universitas Pasir Pengaraian, 2016)
The purpose of this study was to identify the Influence of Land Area, MaintenanceCosts, Revenues and Number of Families Against Rural Farmers Fullness Kingdom.Research methods through direct observation and interviews with the instrument aquestionnaire containing open questions to the respondents in the study area with multiplelinear regression analysis. The result, it was concluded that the higher the land area, cost ofcare, and the number of families of respondents, the higher the income earned. Variablemaintenance costs and land area significantly affect the income of farmers with significantvalue (0.00), but the number of families do not significantly affect the income of farmerswith a significance value (0.051).